2021
DOI: 10.3390/educsci11060300
|View full text |Cite
|
Sign up to set email alerts
|

Are Decision-Making Styles, Locus of Control, and Average Grades in Exams Correlated with Procrastination in University Students?

Abstract: In this paper decision-making styles, locus of control, and average grades in exams are examined as correlates of procrastination in a sample of 185 university students (mainly female students) recruited from mandatory courses for degrees in psychology and pedagogy at the University of Catania (Italy). Method: We used the Decisional Procrastination Scale (Ferrari, Johnson, & McCown, 1995), consisting of five Likert-type items useful for analyzing the procrastination; the Decision-Making Styles (Di Nuovo &a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 52 publications
2
9
0
1
Order By: Relevance
“…Confirming the H2, the freshmen who use dysfunctional decision-making styles tended to postdate the tasks to do and how to do them; it means that the more the freshmen adopt strategies of decision-making ineffective for solving critical situations, the more they tend to procrastinate their choices about the realization of activities or the planning of behaviors to be adopted in various situations such as the academic context. Also in this case, these evidences are in line with the previous results found by Handayani and Andromeda (2017), Sagone and Indiana (2021), but incoherent with those of Santosa (2017); for instance, in the same academic context, Sagone and Indiana (2021) found that the more the university students tend to procrastinate their decisions, the more they are likely to adopt dysfunctional decision-making styles, and the doubtfulness and the delay are predominantly used by the Italian university students attending the Psychology and Pedagogy degree courses. On the contrary, the findings of Santosa revealed an insignificant inverse relationship between decision-making styles (measured using the GDMSQ: Scott, et al, 1995) and academic procrastination (analyzed with the APS: McCloskey & Scielzo, 2015).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Confirming the H2, the freshmen who use dysfunctional decision-making styles tended to postdate the tasks to do and how to do them; it means that the more the freshmen adopt strategies of decision-making ineffective for solving critical situations, the more they tend to procrastinate their choices about the realization of activities or the planning of behaviors to be adopted in various situations such as the academic context. Also in this case, these evidences are in line with the previous results found by Handayani and Andromeda (2017), Sagone and Indiana (2021), but incoherent with those of Santosa (2017); for instance, in the same academic context, Sagone and Indiana (2021) found that the more the university students tend to procrastinate their decisions, the more they are likely to adopt dysfunctional decision-making styles, and the doubtfulness and the delay are predominantly used by the Italian university students attending the Psychology and Pedagogy degree courses. On the contrary, the findings of Santosa revealed an insignificant inverse relationship between decision-making styles (measured using the GDMSQ: Scott, et al, 1995) and academic procrastination (analyzed with the APS: McCloskey & Scielzo, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…According to regression analysis, the results indicated that only one style of decision-making (that is, doubtfulness) and the inhibitory intolerance of uncertainty positively affected decisional procrastination: it means that the freshmen who adopt a style characterized by doubts and emotional interference regarding their choices tend to poorly tolerate the uncertainty. This evidence confirmed the results obtained by Ferrari and Dovidio (2000), Indiana (2021), andMansouri et al (2021). For instance, Mansouri et al (2021) found that decisional procrastination can be predicted by self-compassion, fear of failure, and intolerance of uncertainty in a sample of 440 Iranian post-graduate students.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…It may entail either procrastinating or transferring the responsibility for making decisions to someone else (i.e., buck-passing). Studies have reported performance to be positively related to vigilance (Kornilova et al, 2018) and negatively related to procrastination (Sagone & Indiana, 2021;, but its relationship with the other decision-making styles remains undetermined.…”
Section: Introductionmentioning
confidence: 99%
“…It may entail either procrastinating or transferring the responsibility for making decisions to someone else (i.e., buck-passing). Studies have reported performance to be positively related to vigilance (Kornilova et al, 2018) and negatively related to procrastination (Sagone & Indiana, 2021;Steel, 2007), but its relationship with the other decision-making styles remains undetermined.…”
mentioning
confidence: 99%